Principles for modelling technological processes investigation into the strength and durability of automatic coupler sa‐3 in railway carriages - Daunys, Mykolas; Putnaitė, Donata; Bazaras, Žilvinas (Transport, 2009)
The paper presents the durability analysis of the automatic coupler in railway carriages. The loading of the automatic coupler predetermined by the weight of a train, train speed and railway relief is a time‐dependent variable. The finite element method was used for stress‐strain state calculation taking into account acting forces. In order to reduce stress concentration, the geometry of the automatic coupler's body was modified. Modelling results for different rounded radii demonstrated it was possible to reduce stress concentration up to 34%. Under maximum forces, plastic strain occurs in the automatic coupler's body. The calculation of strain and stress state in the body of the automatic coupler shows it is under a static, low and high cycle loading. Therefore, to calculate the durability of the automatic coupler, the dependencies for low cycle nonstationary stress limited loading has been proposed evaluating low cycle quasistatic and fatigue damages. In order to evaluate high cycle fatigue damage, a linear law for the summation of loading cycles has been suggested. For low cycle damage evaluation, the calculation method for the summation of fatigue and quasi‐static damages created at one loading cycle taking into account loading level and neglecting the sequence of cycles has been put forward. Thus, to calculate the automatic coupler for each specific case, it is necessary to determine the number of loading cycles at each loading level and to evaluate durability considering dependencies presented in this paper.First published online: 27 Oct 2010